Flexibility transition and guest-driven reconstruction in a ferroelastic metal-organic framework - Hunt, S; Cliffe, M; Hill, J; Cairns, AB; Funnell, N; Goodwin, A (Royal Society of Chemistry, 2015)
The metal-organic framework copper(i) tricyanomethanide, Cu(tcm), undergoes a ferroelastic transition on cooling below Tf = 240 K. Thermal expansion measurements reveal an order-of-magnitude variation in framework flexibility across Tf. The low-temperature phase α-Cu(tcm) exhibits colossal positive and negative thermal expansion that is the strongest ever reported for a framework material. On exposure to acetonitrile, Cu(tcm) undergoes a reconstructive solid-phase transition to acetonitrilocopper(i) tricyanomethanide. This transition can be reversed by heating under vacuum. Infrared spectroscopy measurements are sensitive to the phase change, suggesting that Cu(tcm) may find application in solid-phase acetonitrile sensing.